Four inputs and one output current-mode multifunction filter using CDTAs and all-grounded passive components - Kumngern, Montree; Phatsornsiri, Punnavich; Dejhan, Kobchai (My University, 2012)
This paper presents a new current-mode universal filter with four inputs and one output using four current differencing transconductance amplifiers, two grounded capacitors and two grounded resistors. The proposed circuit can realize of low-pass, band-pass, high-pass, band-stop and all-pass current responses, without component-matching conditions and inverting-type input signals requirements. The natural frequency and the quality factor can be set orthogonally and electronically by adjusting the transconductance gains. The filter also offers the features of low input and high output impedances, low active and passive sensitivities and use of only grounded passive components which is ideal for integration point of view. The characteristics of the proposed circuit are simulated using PSPICE simulators to confirm the presented theory. © 2012 IEEE.
Keywords: current differencing transconductance amplifier (CDTA); current-mode circuit; Universal biquadratic filter